Supernumeraries: No more an added number, but an added advantage - Aswathi, T M; Ephraim, Rena; Ayilliath, Ambili; Chandrashekhar, Sharath (Indian Journal of Case Reports, 2020)
In today’s world, extraction of an extra tooth is the rule of thumb and retention is never thought of. Here, we present a case series of two cases in which supernumeraries in the anterior region were retained to the advantage of the patient, for preventing malocclusion, retaining space, and enhancing esthetics of the individual. Supernumerary tooth refers to any tooth in excess of the usual configuration of the normal number of primary or permanent teeth. Its prevalence in permanent dentition is between 0.5% and 5.3% and between 0.2 and 0.8% in the primary. Treatment options involve surgical or conventional extraction. Complications associated with supernumeraries make it important to recognize and manage them early so as to prevent malocclusions and malalignments in permanent dentition. In the first case, supernumeraries were maintained until the eruption of permanent central to preserve space. In the second case, the supernumerary tooth was brought down with orthodontic traction and reshaped to simulate the contralateral tooth.